Cord blood n-3 LC-PUFA is associated with adiponectin concentrations at 10 years of age. (May 2015) - Standl, M.; Demmelmair, H.; Koletzko, B.; Heinrich, J.
Abstract: An elevated ratio of n -6 to n -3 long-chain (LC-) polyunsaturated fatty acids (PUFA) may be a potential risk factor for obesity development. N -3 LC-PUFA are thought to alter adiponectin concentrations, and thus may have a beneficial effect on weight development. We analysed the association between n -3 LC-PUFA concentrations in cord blood and adiponectin concentrations at 10 years. Fatty acid composition was measured in cord blood and at 10 years of age by gas chromatography, and adiponectin concentrations were measured only at 10 years of age in 237 children from the Munich LISAplus birth cohort study. Linear regression models assessed associations between n -3 LC-PUFA, n -6 LC-PUFA and the n -6/ n -3 ratio in cord blood with adiponectin concentrations at 10 years of age. LC-PUFA were presented as percentages and categorized into tertiles. Regression models were adjusted for LC-PUFA percentages at 10 years of age and other potential confounding factors. Cord blood n -3 LC-PUFA tertiles were significantly associated with adiponectin concentrations in an inverse J-shaped relationship [2nd tertile versus 1st tertile: Beta=1.84 (SE=0.65), and 3rd tertile versus 1st tertile: 1.02 (0.68), p -value<0.01 (ANOVA)]. Further, cord blood n -6/ n -3 ratios were significantly associated with adiponectin concentrations [2nd tertile versus 1st tertile: 0.14 (0.67), and 3rd tertile versus 1st tertile: −1.37 (0.68), p -value=0.03 (ANOVA)]. The cord blood n -6 LC-PUFA tertiles were not associated with adiponectin concentrations. Our results suggest that a higher n -3 LC-PUFA concentrations and a lower n -6/ n -3 ratio in cord blood are associated with higher adiponectin concentrations at 10 years of age.